Pendekatan karya berbentuk eksperimentasi - Connie, Anak Tensay (Universiti Malaysia Sarawak (UNIMAS), 2006)
Development in art and technology contribution to new discovery and perception into the varieties of media and process in art. The strong desire of surfing a new technology era challenged the new generation to aspire a new perception in art with a new technology.